A glucose-powered antimicrobial system using organic–inorganic assembled network materials. Issue 4 (24th November 2014) - Yuan, Huanxiang; Bai, Haotian; Liu, Libing; Lv, Fengting; Wang, Shu
Abstract : A new glucose-driven photodynamic antimicrobial system was developed using organic–inorganic network materials encapsulating an enzyme cascade. Abstract : A new glucose-driven photodynamic antimicrobial system was developed to efficiently kill bacteria and fungi, taking advantage of organic–inorganic network materials encapsulating glucose oxidase and horseradish peroxidase and bioluminescence resonance energy transfer (BRET).